An Alevi Female Ashik Nevruza Baci - Gedik, Seda (Journal of Alevism-Bektashism Studies, 2020)
Ashik Nevruza Baci, set about the ashik art through her spouse Ashik Kul Semai who influenced ashiks in his period and after, differs from other female ashiks by becoming an ashik due to a dream. For this reason, Ashik Nevruza Baci is in a different position than her female contemporaries, especially in the period and environment in which she grew up. The environment ashiks grew up in and the belief system they belong to are quite important in their upbringing and poetry. The poetry of Ashik Nevruza Baci, who grew up within the Alevi belief system and the ashik tradition, has traces of the environment she grew up in and the belief system she belongs to. In her poetry, Ashik Nevruza Baci, describing the path that aspirants should follow, especially speaks about Haci Bektash-i Veli and expresses her love for him. According to the Alevism belief, there are certain stages and rules that the person who is on the path of the truth must follow. In order to become a perfect human being and reach the God, the person has to have a guide/mentor, to know itself, to be free of self and to pass the whole of the stages on the path to God respectively. According to the Alevi belief, people can know the God’s secret only when they become perfect human being. For this reason, Ashik Nevruza Baci emphasized in her poems that an aspirant, i.e. the person who wants to become a perfect human being, should pass the stages properly. Moreover, the concept of “musahiplik” (spiritual companionship) also has an important place within the Alevi belief system. Dealing with this concept in her poetry, Ashik Nevruza Baci indicates that she’s also a “musahip”. The aim of this paper is to analyse with the examples Ashik Nevruza Baci’s poems which treat the values of the belief system she belongs to and which were reached through her relatives. Moreover, the paper discusses in detail the life of Ashik Nevruza Baci, her beginnings as an ashik related to the dream motif and the subjects of her poems.
Keywords: Alevism; woman; ashik; dream motif